PENGARUH LINGKUNGAN TERHADAP KEPATUHAN MENGGUNAKAN MASKER DALAM UPAYA MENCEGAH COVID-19 PADA MAHASISWA AKADEMI KEBIDANAN INDRAGIRI TAHUN 2020 - Monifa Putri (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
According to the World Health Organization (2020) Covid-19 is a disease caused by a new coronavirus that was not previously identified in humans. Coronaviruses are a group of viruses found in animals and humans. Indonesia is one of the countries exposed to Covid-19 with the number of cases continuing to increase. Since the announcement of the first case on March 2, 2020-16 December 2020, Covid-19 patients have reached 636,154 people (Kompas.com, 2020). Meanwhile, in Indaragiri Hulu, the total number of suspected Covid-19 cases from March 3, 2020 to December 16, 2020 was 2,612 and 728 confirmed cases (Riau Provincial Health Office, 2020). This study aims to determine the effect of the environment on compliance with using masks on students of the Indragiri Midwifery Academy. This research is analytic by using a cross sectional approach. The sampling technique was total sampling, namely all 48 students of the Indragiri Midwifery Academy, all populations were used as research samples. The data analysis technique used is univariate analysis to describe the independent and dependent variables. Bivariate analysis to see the relationship between two variables, was carried out by chi-square with a significant degree of p < 0.05. The results of the chi-square statistical test obtained a value of P> 0.05 (P = 0.939), it can be concluded that there is no influence between the environment (parents and peers) with adherence to wearing masks.